Correlation Analysis of Biological and Chemical Properties of SoilIn the Third Generation of Oil Palm Plants at PT. Sinar Pandawa Labuhanbatu - Siregar, Erdiansyah; Walida, Hilwa; Hariyati Adam, Dini; Syawal Harahap, Fitra (International Journal of Science and Environment (IJSE), 2023)
The mainstay commodity that can be expected to increase the income and dignity of plantation farmers and Indonesian transmigrants is Palm Oil (Elaeis Guinensis Jacq). Oil palm Soil microbes have an important role in the soil ecosystem which is responsible for the nutrient cycle to maintain soil fertility and structure, especially the biological properties of the soil. This research was carried out through 2 stages of activities, namely field activities and analysis activities. Stages of field activities were carried out at the Kebun Sinar Pandawa Palm Oil Plantation PT. Sinar Pandawa, Labuhanabtu, North Sumatra Province with a height of 28 meters. The method used in this research is a free grid measurement method at a semi-detailed survey level (observation frequency of 1 sample per 500 meters). Carrying out soil sampling at up to 5 sampling points with a distance of 100 meters in the field using a random method, spread over a predetermined area based on the base map. Research Results Land use with different vegetation produces different biological and chemical soil properties. Soil organic C was positively correlated with total microbial population, total fungal population, and respiration. The highest correlation between biological and chemical soil properties was obtained from the total microbial population with a total P of 0.714. The highest correlation was obtained from the correlation between organic C and total N levels, namely 0.947.